2012
DOI: 10.1037/a0026980
|View full text |Cite
|
Sign up to set email alerts
|

Friending, IMing, and hanging out face-to-face: Overlap in adolescents' online and offline social networks.

Abstract: Many new and important developmental issues are encountered during adolescence, which is also a time when Internet use becomes increasingly popular. Studies have shown that adolescents are using these online spaces to address developmental issues, especially needs for intimacy and connection to others. Online communication with its potential for interacting with unknown others, may put teens at increased risk. Two hundred and fifty-one high school students completed an in-person survey, and 126 of these comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
246
2
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(269 citation statements)
references
References 56 publications
(61 reference statements)
12
246
2
9
Order By: Relevance
“…One of the most common online activities for adolescents is communicating with others, primarily individuals known offline (Reich et al, 2012). Use of social networking sites is associated with greater feelings of peer affiliation (Spies Shapiro & Margolin, 2014), and adolescents who use social networking sites report less peer-related loneliness than non-users (Teppers, Luyckx, Klimstra, & Goossens, 2014), suggesting that adolescents who use social networking sites are developing the necessary social skills to have healthy peer relationships.…”
Section: Social Competencementioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common online activities for adolescents is communicating with others, primarily individuals known offline (Reich et al, 2012). Use of social networking sites is associated with greater feelings of peer affiliation (Spies Shapiro & Margolin, 2014), and adolescents who use social networking sites report less peer-related loneliness than non-users (Teppers, Luyckx, Klimstra, & Goossens, 2014), suggesting that adolescents who use social networking sites are developing the necessary social skills to have healthy peer relationships.…”
Section: Social Competencementioning
confidence: 99%
“…In an interview study of 128 American 13 to 14 year olds, 85% reported using information technologies for communication purposes (Fitton, Ahmedani, Harold, & Shifflet, 2013); a study of 10,930 adolescents spanning 6 European countries found that approximately 70% of adolescents aged 14 to 18 years reported using social networking sites daily (Tsitsika et al, 2014). The primary reason why adolescents use social networking sites is to connect with individuals known offline (Reich, Subrahmanyam, & Espinoza, 2012). …”
Section: How the Internet Is Being Used Todaymentioning
confidence: 99%
“…That is to say that online communication is most frequent with those persons we communicate with in person as well. The strong overlap of computermediated and face-to-face communication networks can at least partially be explained by the fact that new communication technologies are diffusing within the pre-existing social structures that are represented by face-to-face communication (Baym et al 2004;Subrahmanyam et al 2008;Neuberger 2011;Reich et al 2012;van Zalk et al 2014). Offline relationships may not only be relevant for the adoption of new communication technologies.…”
Section: Mediatized Construction Of Collectivitiesmentioning
confidence: 99%
“…The growth in technology including social media, texting, and competitive online gaming has affected teenagers' communication during the ensuing years. This has implications both for how social networks form and members communicate with one another (e.g., Reich, Subrahmanyam, & Espinoza, 2012) and for how aggression is carried out among peers with different social status (e.g., Badaly, Kelly, Schwartz, & Dabney-Lieras, 2013). These implications call for an effort to replicate of the current findings with more current and expanded measures of peer group socialization processes and related outcomes.…”
Section: Limitationsmentioning
confidence: 99%